Barriers and Facilitators to Eye Care Among Homeless Adults in Montreal, Canada - Messier, Annabelle; Barré, Victoria; Faucher, Caroline; Tousignant, Benoit (Canadian Journal of Optometry, 2025)
<p class="s3" style="margin-top: 0px; margin-bottom: 0px; line-height: 1.8; text-align: justify; caret-color: #000000; color: #000000; font-family: -webkit-standard; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Purpose <p class="s4" style="margin-top: 0px; margin-bottom: 0px; line-height: 1.8; caret-color: #000000; color: #000000; font-family: -webkit-standard; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">People experiencing homelessness have higher prevalence of health and eye problems than the general population and are less likely to access healthcare services, despite universal healthcarecoverage in Canada. This study aims to describe the competing priorities to healthcare and thebarriers and facilitators to eye care for homeless adults in Montreal (Canada), exploring potential differences between genders. <p class="s4" style="margin-top: 0px; margin-bottom: 0px; line-height: 1.8; caret-color: #000000; color: #000000; font-family: -webkit-standard; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> <p class="s4" style="margin-top: 0px; margin-bottom: 0px; line-height: 1.8; caret-color: #000000; color: #000000; font-family: -webkit-standard; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Methods <p class="s4" style="margin-top: 0px; margin-bottom: 0px; line-height: 1.8; caret-color: #000000; color: #000000; font-family: -webkit-standard; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Cross-sectional study conducted in homeless shelters in Montreal, following stratified randomization. A questionnaire was adapted from existing validated items on competing priorities as well as on barriers and facilitators. Items explored included costs, accessibility and transportation, trust and previous experiences and health literacy. Comparisons were made usingchi-squared and Mann-Whitney U tests. <p class="s4" style="margin-top: 0px; margin-bottom: 0px; line-height: 1.8; caret-color: #000000; color: #000000; font-family: -webkit-standard; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> <p class="s4" style="margin-top: 0px; margin-bottom: 0px; line-height: 1.8; caret-color: #000000; color: #000000; font-family: -webkit-standard; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Results <p class="s4" style="margin-top: 0px; margin-bottom: 0px; line-height: 1.8; caret-color: #000000; color: #000000; font-family: -webkit-standard; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Six shelters for the homeless were approached and accepted to serve as data collection sites. Sixty-two participants completed the questionnaire and 51.6% (n = 32) identified as women. In all, 69.4% (n = 43) of participants had valid eye care coverage. Half of participants (n = 31) hadnot consulted an optometrist or ophthalmologist in ≥ 3 years. Nearly a quarter (24.2%, n = 15) of participants reported having at least one strongly competing priority. Prohibitive costs were the most strongly identified barrier, with a group median score of 4.0 (IQR 2.0-5.0). Complexity of coverage procedures seemed to be a barrier mostly for men (median score 4.0 [IQR 3.0-5.0] on a 5-point Likert scale). Strong facilitators included trust in optometrists (median 1.0 [IQR 1.0-2.0])and having more than one health and social services in the same location (median 1.0 [IQR 1.0-2.0] on a 5-point Likert scale). No statistical differences were found between men and women. <p class="s4" style="margin-top: 0px; margin-bottom: 0px; line-height: 1.8; caret-color: #000000; color: #000000; font-family: -webkit-standard; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> <p class="s4" style="margin-top: 0px; margin-bottom: 0px; line-height: 1.8; caret-color: #000000; color: #000000; font-family: -webkit-standard; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Conclusion <p class="s4" style="margin-top: 0px; margin-bottom: 0px; line-height: 1.8; caret-color: #000000; color: #000000; font-family: -webkit-standard; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">For adults experiencing homelessness in Montreal, despite large coverage for eye care services, competing priorities and prohibitive costs are strong barriers to seeking care. Trust in optometrists and the grouping of health services are notable facilitators. These data may help develop more inclusive strategies for delivering eye care to this underserved population.